Case Witness Data Management Information System at the Military Court I-01 Banda Aceh - Fadhli, Zia; Munawir (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The Case Witness Data Management Information System is an integral component of the operations at the Military Court I-01 Banda Aceh. The primary objective of this system is to manage and organize case witness information, ensure the efficient distribution of evidence, and facilitate information accessibility. This research focuses on the Case Witness Data Management Information System at the Military Court I-01 Banda Aceh, developed using Microsoft Visual Basic.NET as the programming language and Microsoft Office Access as the database management system. The aim of this research is to design and analyze this system using the Microsoft Visual Basic.NET and Microsoft Office Access platform. Data collection was conducted through literature review (examining relevant literature) and field research (interviews and direct observation). The system is managed by one primary administrative staff member, supported by two additional administrative staff, who are responsible for recording and inputting witness data. Research findings indicate that the Case Witness Data Management Information System has been implemented according to established procedures. The system utilizes computer technology, employing Visual Basic.NET and Microsoft Access 2010 as its database management system.